Application of Jigsaw Cooperative Learning Model to Improve Student's Learning Outcomes in Human Excretion System Materials in SMA Private Kemala Bhayangkari-2 Rantauprapat - Fika Riyani; Zunaidy Abdullah Siregar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this study was to improve student learning outcomes in class XI MIA at SMA Private Kemala Bhayangkari-2 Rantauprapat on the material of the human excretory system by applying the jigsaw cooperative learning model. The population in this study were all students of class XI MIA which consisted of four classes with a total of 120 students and the sample in this study was class XI MIA-2 (Control class) which consisted of 30 students and class XI MIA-3 (Experimental class) amounted to 30 students. . Sampling in this study using random sampling (randomly). The data collection technique in this study was using a pretest (pretest) and a final test (posttest). From the research conducted, student learning outcomes in the control class experienced a considerable change in the average value, where in the initial test the average value was 38 and in the final test the average value was 76. Meanwhile, student learning outcomes in the experimental class experienced a significant increase significant where in the initial test the average value is 38.5 and in the final test the average value becomes 85. The results of this study indicate that the jigsaw cooperative learning model can improve the learning outcomes of biology students in learning materials of the human excretory system.